2006
DOI: 10.1093/carcin/bgl093
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of disease-causing MYH mutations in colon cancer families

Abstract: The genetic factors that cause clustering of colorectal cancers (CRCs) other than mutations in the mismatch repair (MMR) genes are not well understood. Clustering in families who lack MMR gene mutations may be attributable to low-penetrance mutations. Hypothetically, mono-allelic MYH mutations could contribute to the risk of CRC in these families. Using Fisher's exact test and logistic regression, we compared the frequency of the known disease-causing MYH mutations Y165C, G382D and 466delE in 137 probands (117… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 28 publications
3
40
0
Order By: Relevance
“…The polyp burden of individuals affected with MAP is variable, and although the data are limited, current evidence suggests that biallelic mutations can be found in up to 30% of patients with 15-100 adenomas and in ~7% of patients with >100 adenomas. 3 Biallelic mutations have been identified in patients with no detectable polyposis.…”
Section: Brief Clinical Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyp burden of individuals affected with MAP is variable, and although the data are limited, current evidence suggests that biallelic mutations can be found in up to 30% of patients with 15-100 adenomas and in ~7% of patients with >100 adenomas. 3 Biallelic mutations have been identified in patients with no detectable polyposis.…”
Section: Brief Clinical Descriptionmentioning
confidence: 99%
“…3 Lynch syndrome and FAP have sometimes also been referred to as Gardner syndrome (FAP with extracolonic features), Muir-Torre syndrome (Lynch syndrome with sebaceous skin lesions), and Turcot syndrome (FAP with medulloblastomas or Lynch syndrome with glioblastomas). Clinical testing for these genes has progressed rapidly in the past few years with advances in technologies and the lower cost of reagents, especially for sequencing.…”
mentioning
confidence: 99%
“…17 Moreover, both biallelic and monoallelic mutation carriers are more likely to have first and/or second-degree relatives with colorectal cancer compared with noncarriers. 29 These observations, as well as those reported on colon cancer families who lack mismatch repair gene defects, 30 suggest that MUTYH heterozygous mutations represent low-penetrance colorectal cancer-causing alleles. On the other hand, recently performed meta-analyses produced conflicting results, indicating both a nonsignificant relative risk of colorectal cancer 31,32 and a small but significantly increased risk of cancer 33 for monoallelic mutation carriers.…”
Section: Germline Defects In Polyposis Patientsmentioning
confidence: 72%
“…The clinical finding of biallelic mutation has been confirmed by subsequent preclinical and clinical studies (Nielsen et al, 2005;Sieber et al, 2004;Tenesa et al, 2006) controls from Scotland, supported by a meta-analysis from published data on the association between mutations at MYH and colorectal cancer risk, has suggested that a small but significant mono-allelic effect may also exist (Farrington et al, 2005). Recent data suggest phenotypic similarities between colorectal cancers characterized by mismatch repair defects and those characterized by biallelic mutation of MYH (Aaltonen et al, 2007;Peterlongo et al, 2006). Other studies are emerging which associate mutations in hMYH with other human cancers such as gastric cancer (Zhang et al, 2006).…”
Section: Dna Glycosylasesmentioning
confidence: 88%